The Effect of Organizational Climate and Knowlegde Sharing on Employee Performance - Utami, Devi Astri (International Humanities and Applied Science Journal, 2020)
This study aims to examine and analyze the effect of organizational climate and knowledge sharing on employee performance. The object of this research is the part of staffing in communication and informatics institutions located in Jakarta. This study was conducted on 30 respondents with this researcher using the sample method: saturated or biases is also called the census method and the data obtained is analyzed using PLS (Partial Least Square) analysis techniques through SmartPLS software. The result is organizational climate has positive and significant effect performance, and knowledge sharing has negative and insignificant effect to employee performance.